DEMIC DEAL-BREAKERS AND THE STATISTICAL IMAGINARY OF THE DIGITAL DIVIDE - Rennie, Ellie (AoIR Selected Papers of Internet Research, 2015)
In this paper I challenge current conceptions of digital inclusion and exclusion as they are conceived through statistical analysis. Drawing on the findings of a multi-year study of internet adoption in remote Aboriginal communities in central Australia, I demonstrate how remote Indigenous sociality is leading to a particular enactment of ‘digital choices’ (Dutton et al. 2007) that cannot be understood through statistics alone. These choices are leading to an ‘all or nothing’ scenario that manifests at the group level as a digital divide. The paper proposes a new theory – the ‘demic dealbreaker’ – to explain differential rates of broadband adoption across remote Aboriginal communities.